Clay mineralogy, strontium and neodymium isotope ratios in the sediments of two High Arctic catchments (Svalbard) - Hindshaw, R; Tosca, N; Piotrowski, A; Tipper, E (Copernicus Publications, 2018)
The identification of sediment sources to the ocean is a pre-requisite to using ocean sediment cores to extract information on past climate and ocean circulation. Sr and Nd isotopes are classical tools with which to trace source provenance. Yet, despite considerable interest in the Arctic Ocean, the circum-Arctic source regions are poorly characterised in terms of their Sr and Nd isotopic compositions. In this study we present Sr and Nd isotope data from the Paleogene Central Basin sediments of Svalbard, including the first published data of river sediments from Svalbard. The bulk sediments exhibit considerable isotopic variation (εNd0 = −24.2 to −11.9; 87Sr/86Sr = 0.72449 to 0.75243) which can be related to the depositional history of the sediments. In combination with analysis of the clay mineralogy of the sediments, we suggest that the Central Basin sediments were derived from two proto sediment sources. One source is Proterozoic sediments derived from Greenland which are rich in illite and have high 87Sr/86Sr and low εNd0 values. The second source is Carboniferous to Jurassic sediments derived from Siberia which are rich in smectite and have low 87Sr/86Sr and high εNd0 values. Due to a change in deposition conditions throughout the Paleogene (from deep-sea to continental) the relative proportions of these two sources varies in the Central Basin formations. The modern river suspended sediment isotopic composition is then controlled by modern processes, in particular glaciation, which determines the present-day exposure of the formations and therefore the relative contribution of each formation to the suspended sediment load. This study demonstrates that the Sr and Nd isotopic composition of river sediment from the continents exhibits significant seasonal variation, which almost certainly mirrors longer-term hydrological changes, with implications for source provenance studies based on fixed sources through time.